Indonesian EFL Learners’ Motivation: An Investigation into Online and Offline Learning in Islamic Higher Education - Ary Setya Budhi Ningrum; Toyyibah (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
This study investigated the learning motivation of English as a Foreign Language (EFL) learners at an Islamic Higher Education institution in Indonesia, comparing their motivation in both online and offline platforms. This study employed a survey methodology by using questionnaires to collect the data. The participant of the study were 76 students. The selected students were those who have experiences of attending both online and offline classes in order to compare their perspectives. The current study evaluates students' motives encompass factors such as readiness, interest, interaction, engagement and satisfaction across language skills namely speaking, listening, reading, writing, and grammar class. Responses from 76 students, together with their comments and suggestions, were used for data analysis. This study found that majority students are more motivated in offline classes than online ones for spoken language skills and grammar class. Meanwhile, for text-based skill such as reading and writing the students shows a nearly equal distribution between online and offline. One important thing in the teaching and learning process that students feel demotivated in online learning is the interaction aspect. Thus, it is recommended that lecturers improve their interaction competencies for running online classes.